Analysis of the thickness of hard tissues in human permanent dentition - Affur, María Constanza (2020)
Objective. To verify the thickness of dental hard tissues at present. Methods. Observational, descriptive and cross-sectional study. Ninety four human permanent teeth existing in the library of the Faculty of Dentistry of the National Northeast University were collected during 2004-2014, these were free of injuries and restorations, with full crowns and root were used. Eight samples from each group (incisors, canines, premolars, and molars) were selected to measure the thickness of hard tissues of incisal, occlusal, central, cervical, and apical thirds. A Model AA flat vice and carborundum discs were used in a Dremel 4000 micromotor to make longitudinal cuts in the mesiodistal direction of each selected piece and the surface was polished with a pumice stone until minimum thickness was obtained. The measurement was made in millimeters with a digital microscope, resolution up to 2M pixel, 25 - 400x. Results. The thickest tissue in all the dental groups was dentin whose value was 1.53 mm to 5.16 mm, enamel followed in order with 0.87 mm to 3.47 mm depending on the location, and the thinnest tissue was cement with values between 0.18 mm and 0.78 mm. The greatest thickness of enamel and dentin was registered in the premolar group, while the greatest thickness of cement, in the molar group. Conclusion. This work has allowed us to observe significant differences in the thickness of the dental tissues, measured in permanent human teeth.